Environmental Determinants of Oral Cancer Development: An Overview - Maddahi, Moein; Ghanbarikondori, Parizad; Amiri, Faezeh; Abdi, Newsha; Jahromi, Amir Moein; Sadeghi Pour, Niki; Allahyartorkaman, Mohammadreza; Moazzam, Farimah (Asian Pacific Journal of Environment and Cancer, 2024)
Overview: This review article delves into the influence of environmental factors on the onset of oral cancer. It examines the crucial part played by air pollution, occupational exposure and sun exposure in the initiation of oral cancer. Methods: For this extensive literature survey, we examined relevant publications centered on environmental causes of oral cancer, taking into account case-control research and environmental exposure appraisals. Our selection consisted of works chosen for alignment with our topic areas, robust methodologies, and recent publishing timelines. Results: Our investigation revealed that air pollution, occupational exposure and sun exposure are significant factors contributing to the development of oral cancer. When present together, they pose an even greater risk. In other words, the combination of these three environmental elements significantly increases the likelihood of oral cancer occurrence. It is crucial to take measures to reduce exposure to occupational exposure, air pollution and UV rays from the sun to mitigate this risk. Conclusion: The emergence of oral cancer arises from an intricate relationship encompassing hereditary and ecological variables. Efforts devoted to prevention ought to prioritize diminishing direct exposure to established threats, refining general wellbeing guidelines, and informing individuals prone to elevated risk circumstances. Expanded exploration stays imperative for illuminating contributions made by obscured ecological facets, notably pollution, plus devising groundbreaking precautionary tactics.